Increasing progressivity in South Africa's personal income tax system - Rasmussen, Emma Helen (School of Economics, 2017)
This dissertation uses NIDS Wave 4 to simulate past, present and future personal income tax progressivity in South Africa. It is divided into two main sections. The first section investigates changes in progressivity between tax years 1996 and 2017. Using the Kakwani index I find increased progressivity over this time period. However, pre-and post-Gini coefficients show decreased progressivity. The second section uses a static, arithmetic microsimulation model to simulate two policies aimed at increasing progressivity: a negative income tax and increased tax rates for high income earners. The negative income tax is shown to significantly reduce inequality, while increased tax rates for high income earners have a limited impact. They also have limited potential for increasing tax revenue, making it unfeasible to finance the negative income tax through such tax increases. A South African negative income tax will either have to be smaller than the levels simulated or financed through other means.